Only IF/TA in the Histological Evaluation of Post-Reperfusion Baseline Biopsies Correlates With Kidney Transplant Outcome - Quirin Bachmann; Carlos Torrez; Maike Büttner-Herold; Bernhard Haller; Flora Haberfellner; Renate Hausinger; Volker Assfalg; Lutz Renders; Kerstin Amann; Uwe Heemann; Christoph Schmaderer; Stephan Kemmner; et al. (Transplant International)
Here, we retrospectively evaluated the informational yield of 338 post-reperfusion kidney transplant biopsies (including 95 living donations) assessed according to BANFF for the histological characteristics interstitial fibrosis and tubular atrophy (IF/TA), glomerulosclerosis, arteriosclerosis, and acute tubular injury (ATI). Associations with delayed graft function (DGF) and death-censored graft survival were explored through Cox-regression analyses. The maximum follow-up time was 11.4 years, with DGF observed in 108 (32%) cases. After deceased donation there was no association between DGF and histologic parameters. Univariable Cox-regression unveiled an association of IF/TA and glomerulosclerosis with long-term death-censored graft survival (HR per 10% increase: IF/TA 1.63; 95% CI 1.17–2.28; p = 0.003; glomerulosclerosis 1.19; 95% CI 1.01–1.39; p = 0.031). In multivariable Cox regression analyses, adjusted for recognized clinical risk variables like expanded criteria donor-status, donor age, history of diabetes, and HLA-mismatches, only IF/TA maintained association over the total observation period in deceased donations and in the total cohort. Arteriosclerosis and ATI were not associated with clinical outcome after deceased donation. Especially ATI did not affect delayed graft function if only deceased donations were considered. Our data underlines the role of organ quality for transplant outcome prior to acute lesions such as ATI during the transplantation process.